Does the Choice of the Halogenated Anesthetic Influence Renal Function during Hemorrhagic Shock and Resuscitation? - Silva, Alexandre Evangelista [UNESP]; Castiglia, Yara Marcondes Machado [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; Roberto, Wellington Matheus [UNESP]; Braz, Leandro Gobbo [UNESP]; Vane, Luiz Antonio [UNESP]; Vianna, Pedro Thadeu Galvão [UNESP]; Braz, José Reinaldo Cerqueira [UNESP] (Taylor & Francis Inc, 2009)
Introduction. Halogenated anesthetics can cause changes in the variables that modify the cardiac output necessary to maintain renal hemodynamic during hemorrhagic shock and resuscitation. However, halogenated anesthetics seem to protect against renal ischemia-reperfusion injury. In a model of pressure-guided hemorrhagic shock in dogs, we studied the comparative effects of three halogenated anestheticshalothane, sevoflurane, and isofluraneat equipotent concentrations on renal responses after resuscitation. Methods. Thirty dogs were anesthetized with 1.0 minimum alveolar anesthetic concentration (MAC) of halothane, sevoflurane, or isoflurane. The dogs were splenectomized and hemorrhaged to hold mean arterial pressure at 40-50 mm Hg over 45 min and then resuscitated with the shed blood volume. Hemodynamic variables were measured at baseline, after 45 min of hemorrhage, and 15 and 60 min after resuscitation. Renal variables were measured at baseline and 15 and 60 min after resuscitation. Results. Hemorrhage induced reductions of mean arterial pressure, filling pressures, and cardiac index (p 0.05), without significant differences among groups (p 0.05). After 60 min of shed blood replacement, all groups restored hemodynamic and renal variables to the prehemorrhage levels (p 0.05), without significant differences among groups (p 0.05), with the exception of sodium fractional excretion, the values for which were significantly higher in isoflurane group, in relation to the other groups after 15 min of re-transfusion (p 0.05), and renal vascular resistance, the values for which remain lower than baseline in halothane group (p 0.05). Conclusions. We conclude that no difference could be detected between choosing equipotent doses of halothane, sevoflurane, or isoflurane in relation to renal variables in dogs submitted to pressure-adjusted hemorrhagic shock and resuscitation.
Keywords: halothane; isoflurane; sevoflurane; hemorrhage; kidney; dogs